(untitled) (Simbiótica. Revista Eletrônica, 2024)
The article presents research on the representation of women in sociology textbooks used in high school. We recorded, compiled, and analyzed textual mentions and visual records from two single-volume collections, discussing the results from the perspective of feminist epistemology and intersectionality. While women are present and more frequent than in natural science books compared to other studies, some relevant points were observed, such as the scarcity of black women, the absence of indigenous women, and the (partial) confinement of women to gender-related topics encapsulated in certain chapters. These considerations may suggest pathways for improving educational materials in such a relevant discipline in the socio-political context as Sociology.